The ShaRInK framework: a holistic perspective on key categories of influences shaping individual perceptions of knowledge sharing. Issue 4 (13th July 2015) - Schauer, Alexander; Vasconcelos, Ana Cristina; Sen, Barbara
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to present a holistic framework, termed ShaRInK (Sharer, Relations, Institution, Knowledge), that depicts key categories of influences that shape individual perceptions of knowledge sharing within an organisational setting. Design/methodology/approach – An exploratory and qualitative case study strategy in which empirical data were gathered from 24 interviewees that were based in four different branches (i.e. China, The Netherlands, the UK and the USA) of a single information technology services organisation. Findings – The findings led to a holistic framework that depicts four key categories of influences that shape knowledge sharing from an individual perspective: attitudes and characteristics of the sharers, relations between the sharers, institutions which act as a united entity on sharer perceptions and knowledge itself. Furthermore, the four key influences not only shape knowledge sharing independently but are intertwined and have a synergistic effect. The ShaRInK framework is formed by combining these. Originality/value – The findings indicate that knowledge sharing from an individual-level perspective is a more complex phenomenon than currently portrayed in the literature. All four key influences, each being fundamentally different in nature, and their relationships should be taken into account. Equally, the ShaRInK framework can be applied by organisations when developing a knowledge-sharing strategy or auditing existing strategies.